Ovulation time and ovulated eggs count of sneakehead Channa striata induced by prostaglandin 2α with different doses - Frits Jamlaay; Maheno Sri Widodo; Abd. Rahem Faqih (Jurnal Akuakultur Indonesia)
ABSTRACT